Asymmetric Synthesis of Pipecolic Acid and Derivatives - Cant, Alastair A.; Sutherland, Andrew (Synthesis, 2012)
The nonproteinogenic α-amino acid, l-pipecolic acid and its derivatives are components of a wide range of pharmacologically active compounds. The significant biological activity of these compounds has resulted in the development of many synthetic approaches for their preparation. This review highlights these key methods as well as the application of these compounds for the preparation of enzyme inhibitors, conformationally restricted building blocks and peptidomimetics.1 Introduction2 Chiral Pool Approaches2.1 From Amino Acids2.2 From Carbohydrates3 Asymmetric Reactions3.1 Auxiliary-Based Approaches3.2 Catalytic Asymmetric Methods4 Chemoenzymatic Methods4.1 Enzymatic Kinetic Resolution4.2 Miscellaneous Enzymatic Methods5 Synthesis of Pipecolic Acid Derivatives for Biological Applications5.1 Synthesis of Novel Medicinal Agents5.2 Synthesis of Conformationally Restricted Building Blocks (Peptide and Nucleic Acid Mimics)6 Conclusions
Keywords: amino acids; heterocycles; piperidines; asymmetric synthesis; asymmetric catalysis